Research of technologies for manufacturing film thermoelements (BI2TE3) and (SB2TE3) in modern thermoelectric technologies (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article is devoted to the study of the manufacture and practical application of film thermoelements, such as Bi2Te3 and Sb2Te3, in modern thermoelectric technologies. Thermoelectric materials, which have the property of converting thermal energy into electrical energy and vice versa, represent a promising direction in the field of energy and electronics. The article includes review materials on the structural and electrical characteristics of Bi2Te3 and Sb2Te3 film thermoelements, and also provides the results of experimental studies related to their thermoelectric properties. Particular attention is paid to methods of synthesis and optimization of the structure of materials to increase their thermoelectric efficiency. Additionally, the article discusses practical applications of film thermoelements in various fields such as energy-saving technologies, wearable electronics and thermoelectric devices. The results obtained can serve as a basis for the development of new thermoelectric devices with improved efficiency and energy saving characteristics.
Keywords: Film thermoelements, thermoelectric materials, bismuth telluride (Bi2Te3), antimony telluride (Sb2Te3), thin films, magnetron sputtering, chemical vapor deposition (CVD), thermal evaporation, thermoelectric efficiency, Seebeck coefficient, nanotechnology, manufacturing technology, research of thermoelectric properties, energy, cooling technology